Sosialisasi Pentingnya Keselamatan Berlalulintas Bagi SDN Jakasampurna III Kota Bekasi Selama Pademi Covid - Rr. Endang Wahyuni; Deslida Saidah; Subandi Subandi (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of this service activity is to provide understanding and understanding for students in grades 1-3 at SDN Jakasampurna III-Bekasi, with the hope that students will be more orderly in traffic. Early knowledge will foster awareness of safe and secure traffic, and become a good habit in orderly traffic. The problem faced by the school is that the awareness of elementary school students in traffic towards safety and security is very low, every year there are always accidents involving students and road users, the school environment is crowded and various vehicles pass, so that it makes traffic jams during school time. This socialization activity was held on Saturday, April 19, 2022 at SD Negeri Jakasampurna III Bekasi City with 50 participants. The implementation method is Face-to-face Learning (PTM) using animated videos, songs and Power Point. The implementation stages consist of: 1) Reviewing the location of the school; 2) Visiting the school and interviewing the Principal of SD Negeri Jakasampurna III Bekasi City; 3) Determine the problems faced by the school and identify the existing equipment in the school; 4) Implementation of Socialization.